Using of Multi-Criteria Decision-Making Methods in Waste Selection - Eren Batu Günaydın; Oğuzhan Turan; Hasan Bilgehan Kaplan; Mehmet Kaan Temiz; Mehmet Pınarbaşı (Doğal Afetler ve Çevre Dergisi)
Waste is defined as materials resulting from production processes that can no longer be used. Production facilities have to dispose of these wastes in accordance with technical and legal requirements. The selection of suitable waste is an essential process for contractor firms to fulfill their environmental responsibilities and maximize economic benefits. This selection is influenced by many criteria, such as profitability, continuity of supply, toxicity and water ratio, and calorific value. In this study, multi-criteria decision-making methods are used to identify and evaluate these criteria. First, the importance levels of the criteria were calculated using the Analytic Hierarchy Process (AHP). Then, the identified alternatives were ranked by the TOPSIS method. The combined use of AHP and TOPSIS methods has enhanced objectivity in the decision-making process, enabling a more systematic evaluation of alternatives. With the group decision-making approach, 12 criteria were determined in line with the opinions received from the experts. In the results, “Purchase Cost” was found to be the most effective criterion, and “Disposal Method” was found to be the least effective criterion. The study aims to contribute to decision-making processes by guiding contractor firms in establishing efficient and effective waste selection processes.